2014
DOI: 10.5586/aa.2014.056
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the secretory structures in the flowers of Rosa rugosa Thunb.

Abstract: <p>Due to the presence of secondary metabolites exhibiting pharmacological activity, the flowers of <em>Rosa rugosa</em> Thunb. have found application in traditional and folk medicine. The essential oil obtained from them is also considered to be a phytoncide. The morphological and anatomical characters of glandular trichomes located on the sepals of <em>R. rugosa </em>were studied by light and scanning electron microscopy. Using histochemical tests, the type of secretion produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The anatomical structure of Rosa damascena flowers was shown similarity with Rosa rugosa thunb. flowers in terms of glandular hair structures, druses, papillae with the petal surface, cuticular striations on the petal surface [32]. Besides, no different findings were observed in the powdered drug samples purchased from the market and standard sample with the conducted anatomical studies.…”
Section: Discussionmentioning
confidence: 82%
“…The anatomical structure of Rosa damascena flowers was shown similarity with Rosa rugosa thunb. flowers in terms of glandular hair structures, druses, papillae with the petal surface, cuticular striations on the petal surface [32]. Besides, no different findings were observed in the powdered drug samples purchased from the market and standard sample with the conducted anatomical studies.…”
Section: Discussionmentioning
confidence: 82%
“…Due to the presence of secondary metabolites exhibiting pharmacological activity, the flowers of R. rugosa are applied in traditional and folk medicine. The essential oils obtained from them are also considered to be phytoncides [4]. Petals of the R. rugosa flowers are valued as raw material, while rose oil [5,6], is used in health therapy instead of fruits [7].…”
Section: Introductionmentioning
confidence: 99%
“…The flowers of R. rugosa are also used as an agent counteracting toxins, among others as an antidote in antimony intoxication, improving appetite and function of kidney. It has been also shown that rose oil can be included in active phytoncides affecting microorganisms resistant to antibiotics [4][5].…”
Section: Introductionmentioning
confidence: 99%